2022
DOI: 10.3390/ijerph19052504
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced by Italian Nursing Home Staff in End-of-Life Conversations with Family Caregivers during COVID-19 Pandemic: A Qualitative Descriptive Study

Abstract: End-of-life conversations are among the most challenging of all communication scenarios and on the agenda of several healthcare settings, including nursing homes (NHs). They may be also difficult for experienced healthcare professionals (HCPs). This study explores the difficulties experienced by Italian NH staff in end-of-life conversations with family caregivers (FCs) during COVID-19 pandemic to uncover their educational needs. A qualitative descriptive study based on inductive thematic analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 62 publications
0
48
0
Order By: Relevance
“…Reduced frequency and completeness of care plans was found to lead in some cases to uncertain and reactive decisions being made, even 7 months into the pandemic. 35,39 Similarly, Gonella et al 30 identified that some staff in care homes had difficulty exploring relatives' preferences for care at the end of life due to a lack of detail in the advance care directives.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduced frequency and completeness of care plans was found to lead in some cases to uncertain and reactive decisions being made, even 7 months into the pandemic. 35,39 Similarly, Gonella et al 30 identified that some staff in care homes had difficulty exploring relatives' preferences for care at the end of life due to a lack of detail in the advance care directives.…”
Section: Discussionmentioning
confidence: 99%
“…34 The reduced face-to-face contact during the pandemic also appeared to take an emotional toll on relatives and surrogates involved in care planning. 30,33,35 Emotions such as denial and shock concerning a loved one's condition (particularly in the case of acute COVID-19 diagnosis) seemed to be triggered by relatives' reduced ability to directly observe changes over time. 30,31 Although synthesis suggests these circumstances can lead to a greater risk of interventional and curative orientated decisions by relatives, 29,30,35 it was found that frequent ongoing involvement of relatives in care planning conversations can help to mitigate these emotions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations